Analisa ekonomi budidaya kerapu macan (Epinephelus fuscoguttatus) dan kerapu bebek (Cromileptes altivelis) dalam keramba jaring apung di Indonesia - Farok Afero (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. This study presents an economic analysis of tiger and humpback grouper at different production scales in Indonesia. The results highlight the nonviability of small scale tiger grouper, with a 5 years projected negative cumulative cash flow of – Rp. 18.102.650 and a negative net present value (NPV) of – Rp. 22.059.576. An increasing production scale of tiger grouper highlight a marginal viability for medium scale (with a 5 year projected cumulative cash flow of Rp. 198.320.673 and a positive NPV of Rp. 105.578.440; with a benefit cost ratio of 1,25; an internal rate of return (IRR) of 88%; and a payback period of 0,99 year), and an economically viable of large scale cage culture (with a 5 year projected cumulative cash of Rp. 707.746.923; a NPV of Rp.406.801.749; a benefit cost ratio of 1,33;an internal rate of return of 157%;and a payback period of 0,57 year). The economic analysis of humpback grouper atdifferent production scales highlight positive cumulative cash, a positive NPV,a benefit cost ratio higher than 2, an internal rate of return over 300% and apayback period of less than one year. A sensitivity analysis revealed thatincreased survival rate up to 80% would increase cumulative cash and NPV ofsmall scale tiger grouper cage culture. Additionally, improved profitabilityperformance was associated with decreased major production costs, increasedproduction and price of the product.